Extreme Poverty Trap In Kalimantan Barat - Fatmawati Fatmawati; Preatin Preatin (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2022)
Poverty is complex, conceptually and empirically, because it will affect how to understand poverty, its analysis, and policy formulation to overcome poverty. World Bank defines International Poverty Line (GK) as US$ 1.9 as it adjusts for inflation and living standards. Indonesia's poverty rate released by BPS uses a monetary approach, GK, which represents the minimum amount of money a person needs to meet food needs, equivalent to 2100 calories and other non-food needs. Ordinal regression Partial Proportional Odds Model (PPOM) found the best model with independent variables: Number of Household Members, Age, Defecation Facilities, Diplomas, Lightning, Main Activities, and Access to Clean Water, and all these variables significantly affect the status of poor both Extreme Poor, Poor, and Near Poor levels. It was found that Odds Ratio was very different at the Extreme Poor level. It was concluded that this category had different tendencies from other levels. Handling the extreme poor with various conditions requires different handling than the poor. Extremely poor with one household member, aged 1-14 years and 60 years and over, more in need of Social Assistance from the government. Extreme Poor with certain other conditions requires more research to determine the most effective alleviation program.